Classical Music in the Shah and Rana Era: 1768 - 1951 A.D. - Pokharel, Ramesh (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
The tradition of classical music was more justified during the Shah and Rana Dynasty’s ruling. During the time the cultural import from neighboring India and the wide appreciation of music by kings and the Royal Palace of Nepal show the influence of Classical music among the Shah and Rana families. Some Rana Prime Ministers wanted to promote classical music but in practice most music was limited to the Royal palace and Rana family. Music Education, as well as all kinds of formal education were banned for the citizens of Nepal during the Rana regime. Those who were close to the Rana family and the palace were supposed to learn classical music from the patronized Ustaad /Pundit of the Palace and private teachers as well. This paper attempts to discuss the overall developing trends of classical music during Shah and Rana periods of Nepal in relation to development, extension and its practices in Nepalese society. All evidences have been taken from several documentaries. Whatever we practice as classical music today has taken the step of development in those periods. The evidence shows that especially raga based different Music genres were practiced and flourished in those periods.